Revisiting English Proficiency in the Age of Emi: A Systematic Literature Review (2021 – 2025) - Charlize Canol; Melbourne Puntalba; Oleia Czarane Salcedo; Kristine Monique Velano; John Rey Pelila (Journal of English Language and Pedagogy (JELPA), 2026)
Despite extensive research on EMI, important gaps remain regarding proficiency standards, long-term language development, teacher language readiness, and the factors influencing student success. This review addresses these gaps by synthesizing current evidence on English proficiency in EMI contexts and identifying key areas for future research and policy development. This study employed a systematic literature review of 29 peer-reviewed international articles published between 2021 and 2025, using thematic analysis to examine discrepancies, common themes, and emerging patterns related to English proficiency and EMI. The findings show that EMI can enhance receptive skills such as reading and listening, academic vocabulary, and overall language skills; however, its effectiveness strongly depends on students’ initial proficiency, instructors’ linguistic competence, pedagogical strategies, affective factors, socioeconomic status, multilingual practices, and institutional support. Two distinct learner pathways emerge: some learners gain confidence and perform well when they have adequate support and sufficient proficiency backgrounds, whereas others with limited proficiency, increased cognitive demands, or restricted exposure to English continue to struggle. Therefore, it can be concluded that EMI can help improve English proficiency, but only when institutions ensure that instructors possess adequate knowledge and skills, proficiency expectations are clearly defined, and sustained language support is provided to address learners’ needs.